Epidemiology of Injuries in National Collegiate Athletic Association Women's Field Hockey: 2014–2015 Through 2018–2019 - Nedimyer, Aliza K. (J Athl Train, 2021)
CONTEXT: The National Collegiate Athletic Association has sponsored women's field hockey since 1981, and team membership as well as student-athlete participation has grown over time. BACKGROUND: Routine examinations of injuries sustained by athletes are important for identifying and understanding patterns that can be used to inform sport safety practices. METHODS: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program from 2014–2015 through 2018–2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. RESULTS: The overall injury rate was 6.27 per 1000 athlete-exposures (AEs). Head/face injuries (16.0%) and thigh injuries (12.3%) were the most commonly injured body parts during the 2014–2015 through 2018–2019 academic years. Concussion (8.6%) was the most commonly reported injury, and concussion rates notably decreased between 2017–2018 and 2018–2019. SUMMARY: Study findings were generally consistent with the existing epidemiologic evidence. Incidence rates and trajectories of commonly observed injuries warrant particular attention in the future.